Socialization of Jo Kawin Bocah as an Effort to Reduce Early Marriages for Vulnerable Groups - Anisa Putri Adji; Pramudya Ananti; Rhenald Daeng Lommpo; Muhammad Ali Equatora (Indonesian Journal of Community Services, 2023)
Early marriage in Indonesia is a problem that is not only related to marriage law but also related to issues of child protection and human rights. The Parole and Probation Office as an institution that also plays a role in handling Juveniles involved with the law shows its involvement and collaborates with the Women's Empowerment Service, Child Protection, Population Control and Family Planning (DP3AP2KB). Central Java created a program to prevent child marriage called Jo Kawin Bocah, but not all teenagers know about the program. The aim of conducting outreach is to reduce the rate of early marriage among Indonesian children and disseminate information related to the program. The research method consists of counseling and field practice. Reducing the rate of early marriage, especially in communities with low levels of education, is one movement to realize the success of the program.